The Psychology of Resistance to Change: The Antidotal Effect of Organizational Justice, Support and Leader-Member Exchange - Rehman, Nabeel; Mahmood, Asif; Ibtasam, Muhammad; Murtaza, Shah Ali; Iqbal, Naveed; Molnár, Edina (Frontiers in Psychology, 2021)
In today’s business environment, the survival and sustenance of any organization depend upon its ability to introduce a successful change. However, in implementing a change, one of the biggest problems an organization faces is resistance from its employees. The current paper addresses this problem by examining the role of organizational justice dimensions in coping with the resistance to change through the intervening role of perceived organizational support (POS), leader-member exchange (LMX), and readiness for change (RFC) in a sequential framework. Data of 372 employees have been collected from the banking industry of Pakistan. The results obtained through the Partial Least Squares- Structural Equation Modeling (PLS-SEM) approach using SmartPLS suggest that distributive justice, procedural justice, and interactional justice play a critical role in lowering the resistance to change through POS, LMX, and RFC, contributing significantly to the theory and practice. Furthermore, this study also discusses recommendations for future research and limitations associated with this research work.